2022
DOI: 10.7759/cureus.25494
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Origin of the Right Coronary Artery: An Uncommon Presentation

Abstract: The anomalous origin of the coronary artery is a relatively uncommon condition with a variant incidence depending on the modality of the imaging techniques such as transesophageal echocardiography (TEE), computed tomography angiography (CTA), magnetic resonance angiography (MRA), or invasive coronary angiography (ICA). The importance of diagnosing ectopic coronary artery origin comes from its possible relation to sudden cardiac death (SCD) cases in young populations. The anomalous origin of the coronary artery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…The origin and course of abnormal coronary arteries can be visualized with a three-dimensional anatomical display using axial reconstructions from multidetector CTA. Some authors advocate using CT as the first-line investigation when CAA is suspected, as the exact position and course of the anomalous artery can be viewed about the aortic root and pulmonary artery (Shaban et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The origin and course of abnormal coronary arteries can be visualized with a three-dimensional anatomical display using axial reconstructions from multidetector CTA. Some authors advocate using CT as the first-line investigation when CAA is suspected, as the exact position and course of the anomalous artery can be viewed about the aortic root and pulmonary artery (Shaban et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Anomalous origin of the right coronary artery is uncommon, with a reported incidence of 0,26% (Shaban et al, 2022). An anomalous origin of the right coronary artery is usually asymptomatic (Villa et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…AAOCA, including ARCA-L, is a potentially lethal condition associated with malignant arrhythmia, stenocardia, myocardial infarction, and SCD in young adults, highlighting the need to diagnose AAOCA and ARCA-L [ 5 , 14 ]. D’Ascenzi et al [ 15 ] reported that AAOCA accounts for 7.2% of the SCDs in athletes and 1.9% of the SCDs in non-athletes.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients do not exhibit symptoms or only experience them after strenuous physical activity. Nonetheless, patients can present with angina, myocardial infarction, syncope, arrhythmia, or sudden cardiac arrest [ 16 , 17 ]. The onset of symptoms is unpredictable, and the first symptom may be SCD.…”
Section: Discussionmentioning
confidence: 99%